(untitled) (Научни трудове на УНСС, 2025)
As a powerful global sport, Formula 1 (F1) has always been an attractive platform for brands. While the sport’s commitment to sustainability is already an inseparable part of the F1 teams’ activities, very little is still known about how it is reflected in sponsorship relationships. However, the link between sponsorship and sustainability is not straightforward. This is because sport sponsorship is traditionally associated with commercial motives by exploiting rights over sport properties, while the concept of sustainable development is perceived as a moral imperative. The study seeks to interrogate the level of adoption of the sustainability concept in F1 commercial sponsorships from the sponsors’ point of view. A mixed method involving a questionnaire and a semi-structured interview were used to gather information from 18 F1 sponsoring brands, representing both B2B and B2C companies. The results demonstrate that although sustainability is integrated into the corporate ethos, it does not appear as a key criterion in the brands’ decision-making process. It is also illustrated by actual sponsorship priorities by B2B and B2C companies, both of which highlight the importance of factors related to sales. In general, marketing managers have a rather narrow perspective on sponsorship leverage, viewing it merely as a promotional tool within their companies’ marketing mix rather than a strategic platform or a catalyst for achieving a broader set of corporate brands and/or sustainability objectives.